NOVEL NONCLASSSICAL MHC CLASS IB GENES ASSOCIATED WITH CD8 T CELL DEVELOPMENT AND THYMIC TUMORS - Goyos, Ana (2009)
In jawed vertebrates, the heterogeneous nonclassical MHC class Ib (class Ib) gene family encodes molecules structurally similar to classical MHC class Ia (class Ia) but with more limited tissue distribution and lower polymorphism. In mammals, class Ib gene products are involved in stress responses, malignancy and differentiation of intrathymic CD8 T cells. The frog Xenopus laevis possesses at least 20 class Ib genes (XNCs), and 9 subfamilies have been defined so far. We have characterized two novel subfamilies, XNC10 and XNC11. XNC10 is phylogenetically and structurally distinct from both class Ia and other XNC genes. Besides thymic lymphoid tumors, XNC10 is preferentially expressed by circulating T cells and thymocytes of the CD8 lineage both in adult and in larvae from the onset of thymus organogenesis. XNC11 is expressed only by thymocytes and upregulated by several thymic lymphoid tumors. These data provide the first evidence of the expression of any class Ib genes in Xenopus larvae, and suggests evolutionary relationships between certain class Ib genes, malignancy and CD8 T cell ontogeny.